SHIFTING PARADIGMS IN EDUCATIONAL ASSESSMENT: LEARNER-CENTEREDMETHODS (Universal International Scientific Journal, 2026)
In recent decades, assessment in education has undergone a significant shift fromtraditional teacher-centered testing toward more learner-centered approaches that emphasize activeparticipation, autonomy, and meaningful learning outcomes. Contemporary learner-centered assessmentmethods aim to capture not only learners’ final products but also their learning processes, competencies, andreal-world performance. This article provides a critical overview of key learner-centered assessmentapproaches, including project-based assessment, performance-based assessment, portfolio-based assessment,and self- and peer-assessment. Drawing on recent theoretical and empirical studies, the paper examines theprinciples, pedagogical value, and practical implementation of these methods across educational contexts.Particular attention is given to their role in fostering higher-order thinking skills, learner autonomy,reflective practice, and authentic assessment of competencies. By synthesizing current perspectives, thisstudy contributes to a deeper understanding of learner-centered assessment as a sustainable and effectivealternative to traditional testing practices in modern education.
Keywords: learner-centered assessment; alternative assessment; formative assessment